Condition monitoring on bearing faults of electric motor - based on vibration signal - Nur Akmaliza Ali Raus
This final year project is about to measured the vibration signal produce by different types of bearing condition, to analyzed the data for determine the condition of the bearing, and to plot a graph using Matlab Programming and it will become an indicator for future benefit.